The riveting cellular structures of apicomplexan parasites - Harding, Clare R.; Frischknecht, Friedrich (Trends in parasitology, 2020)
Parasitic protozoa of the phylum Apicomplexa cause a range of human and animal diseases. Their complex life cycles - often heteroxenous with sexual and asexual phases in different hosts - rely on elaborate cytoskeletal structures to enable morphogenesis and motility, organize cell division, and withstand diverse environmental forces. This review primarily focuses on studies using Toxoplasma gondii and Plasmodium spp. as the best studied apicomplexans; however, many cytoskeletal adaptations are broadly conserved and predate the emergence of the parasitic phylum. After decades cataloguing the constituents of such structures, a dynamic picture is emerging of the assembly and maintenance of apicomplexan cytoskeletons, illuminating how they template and orient critical processes during infection. These observations impact our view of eukaryotic diversity and offer future challenges for cell biology.